Accessibility, entropy and the distribution and assignment of traffic - Erlander, Sven (Transportation research, 1977)
The entropy of the trip matrix is used as a broad measure of accessibility within a transportation system. An optimizing model which minimizes average generalized trip cost subject to constraints on the entropy is showed to have the gravity model with exponential separation function as its solution. The relation to entropy-maximizing formulations is discussed. The transportation problem of linear programming and a trivial solution are obtained as limiting cases. Extensions to the combined distribution and assignment problem and a bus problem are pointed out.